Relación entre la Actividad Física y la Presencia de Cardiopatías Coronarias en los Adultos Mayores del Centro Poblado Virgen del Carmen, la Era 2008 - Mary Luz Solórzano Aparicio (2019)
Purpose: To determine the relationship between physical activity and the presence of coronary cardio pathologyin senior citizens from the Virgen del Carmen Community, La Era, Lima, Peru 2008. Methodology: Thepresent research was a non-experimental, cross-sectional study; for this purpose it was utilize a survey referentto physical activity for the Virgen del Carmen Community senior citizens, whose age were between 65 yearsold to older, performed during the months of October, 2008. The sample was obtained from 65 senior citizenswho were home visited. Results: The previous reference about the type of exercise performed was soccer asthe most practiced, 27.7%. In the same way the majority performed exercises every day, 47.7%. At the presentthe major group practice walking as their exercise, 72.3%; and they perform it every day, 53.8%. In referenceabout the presence of coronary illnesses it was discovered that the majority of these senior citizens did notpresent the illness 86.2%, while13.8% did show this type of illness. Conclusions: Therefore, it is determinedthat there is a relationship between physical activity performed at the present and the presence of coronaryillnesses, in other words senior citizens who presently practice a physical activity tend not to present coronaryillnesses.